Evaluation of User Satisfaction and Trust of Review Platforms: Analysis of the Impact of Privacy and E-WOM in the Case of TripAdvisor - Martínez-Navalón, Juan-Gabriel; Gelashvili, Vera; Gómez-Ortega, Alba (Frontiers in Psychology, 2021)
Technological advances have had many advantages like an E-WOM (Electronic Word of Mouth) that has become a very important and powerful tool for users who wish to share their knowledge, experiences and emotions about a product or service. But the use of virtual platforms may affect the privacy of users data. This present study has a twofold objective: first check if the privacy of users when using TripAdvisor, the world's largest travel platform, has an impact on their satisfaction and trust on the platform. Secondly, the relationship between E-WOM and the variables users trust and satisfaction when using TripAdvisor is examined. In order to achieve the objectives set out, the sample of 390 persons was analysed. The PLS-SEM method has been used to process the data and test the hypotheses. The results of the analysis have shown that there is a positive and direct relationship between TripAdvisor users' privacy and satisfaction. The direct and positive relationship between users' E-WOM and their degree of satisfaction and trust towards the platform has also been confirmed. This study makes a significant contribution to the academic literature on the variables studied, as previous studies presented different results.